Greater traditionalism predicts COVID-19 precautionary behaviors across 27 societies - Theodore Samore; Daniel M. T. Fessler; Adam Maxwell Sparks; Colin Holbrook; Lene Aarøe; Carmen Gloria Baeza; María Teresa Barbato; Pat Barclay; Renatas Berniūnas; Jorge Contreras-Garduño; Bernardo Costa-Neves; Maria del Pilar Grazioso; et al. (Scientific Reports, 2023)
Abstract People vary both in their embrace of their society’s traditions, and in their perception of hazards as salient and necessitating a response. Over evolutionary time, traditions have offered avenues for addressing hazards, plausibly resulting in linkages between orientations toward tradition and orientations toward danger. Emerging research documents connections between traditionalism and threat responsivity, including pathogen-avoidance motivations. Additionally, because hazard-mitigating behaviors can conflict with competing priorities, associations between traditionalism and pathogen avoidance may hinge on contextually contingent tradeoffs. The COVID-19 pandemic provides a real-world test of the posited relationship between traditionalism and hazard avoidance. Across 27 societies (N = 7844), we find that, in a majority of countries, individuals’ endorsement of tradition positively correlates with their adherence to costly COVID-19-avoidance behaviors; accounting for some of the conflicts that arise between public health precautions and other objectives further strengthens this evidence that traditionalism is associated with greater attention to hazards.